Coupled Heat and Mass Transfer Analysis of an Adiabatic Dehumidifier – Unique Approach. (December 2016) - Naik, B. Kiran; Soni, Ankit; kumar, Amit; Muthukumar, P.; Somayaji, C.
Abstract: Liquid desiccant dehumidifier is one of the most desirable systems for dehumidification of air when compared to conventional refrigeration system and solid desiccant based dehumidifier. In the present study, a finite difference model is developed to simulate the coupled heat and mass transfer processes occur in a counter flow adiabatic dehumidifier employing lithium chloride (LiCl) as a desiccant solution. Mat-lab R13 is used as a simulation package for solving the aforementioned model. This model has taken into the consideration of thermal effectiveness, effective height and moisture effectiveness as variable parameters for obtaining the correlation of the desired operating parameters. The predicted numerical parameters for absorption process have good agreement with the experimental data reported in the literature. This model is unique and can be extended to any type of liquid desiccant solution by changing the solution properties. The performance analysis of adiabatic counter flow dehumidifier is also carried out by varying the operating parameters and the detailed results are presented in the full manuscript.